2004
DOI: 10.1161/01.hyp.0000143852.48258.f1
|View full text |Cite
|
Sign up to set email alerts
|

NO Synthase Inhibition Increases Aldosterone in Humans

Abstract: Abstract-To test the hypothesis that NO influences aldosterone production in humans, we examined the effect of N G -nitro-L-arginine methyl ester (L-NAME) on aldosterone concentrations in the presence and absence of the NO precursor L-arginine (3 g TID) and the angiotensin-converting enzyme inhibitor ramipril (10 mg QD). Ten normal subjects were given L-NAME (66 g/kg per min for 30 minutes) or vehicle in random order on separate days during placebo and after randomized, double-blind treatment with L-arginine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…As we have reported previously in a subset from this study, 24 L-NAME increased circulating aldosterone concentrations compared with vehicle during placebo (Pϭ0.013 for the current study), L-arginine (Pϭ0.031), and ramipril (Pϭ0.049) but not during combined treatment with L-arginineϩramipril (Pϭ0.236). There was no effect of L-NAME on PRA, Ang II concentrations, or NO metabolites (data not shown).…”
Section: Effect Of Acute L-name Infusion On the Raas No Metabolitessupporting
confidence: 81%
See 1 more Smart Citation
“…As we have reported previously in a subset from this study, 24 L-NAME increased circulating aldosterone concentrations compared with vehicle during placebo (Pϭ0.013 for the current study), L-arginine (Pϭ0.031), and ramipril (Pϭ0.049) but not during combined treatment with L-arginineϩramipril (Pϭ0.236). There was no effect of L-NAME on PRA, Ang II concentrations, or NO metabolites (data not shown).…”
Section: Effect Of Acute L-name Infusion On the Raas No Metabolitessupporting
confidence: 81%
“…As reported previously, after screening, subjects were given placebo tablets for 2 weeks. 24 On the mornings of the 12th and 14th days of placebo, subjects reported to the Vanderbilt General Clinical Research Center (GCRC) for infusion of L-NAME (Clinalfa AG) or vehicle (normal saline) in randomized order during normal sodium intake. At the end of the second infusion day, subjects were randomized to double-blind treatment with L-arginineϩplacebo, ramiprilϩplacebo, or L-arginineϩramipril for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…36 Indeed, nitric oxide production has been shown both to increase renin release and to decrease aldosterone secretion and a deficiency in its production may therefore lead to a pattern of high plasma aldosterone and low renin levels. 37,38 Both studies also point out to a stronger participation of aldosterone in the development of human hypertension than expected from the investigations in animal models that have more emphasized the role of renin and angiotensin. 39 They suggest that a pharmacological therapy aimed at decreasing aldosterone synthesis would be useful if the correction of a high aldosterone status present before blood pressure rise is able to prevent it, as does a renin-angiotensin system pharmacological blockade.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, later studies by the same group observed that NO inhibition of aldosterone biosynthesis was cGMP independent, and reversed by the NOS inhibitor thiocitrulline . In vivo studies in human subjects also showed that inhibition of NOS with L-NAME increased aldosterone levels (Muldowney et al 2004).…”
Section: No and Steroidogenesismentioning
confidence: 93%